The Liars Society - Gerber, Alyson (New York : Scholastic Press, 2024)
"Weatherby is a fish out of water. When she lands a scholarship to the prestigious Boston School, she's excited to be in the same world as her dad, whom she's never met, and make real friends. But Weatherby has a secret she'll risk everything to protect, one that could destroy her new life. Every member of Jack's wealthy and privileged family has made their mark at the Boston School. Everyone, that is, except for Jack, who is entirely mediocre. He's desperate to prove his worth to his influential father. But Jack has a secret of his own"--
Keywords: Preparatory schools -- Juvenile fiction; Secret societies -- Juvenile fiction; Social classes -- Juvenile fiction; Family secrets -- Juvenile fiction; Sailing -- Juvenile fiction; Deception -- Juvenile fiction; Families -- Juvenile fiction; Preparatory schools -- Fiction; Secret societies -- Fiction; Social classes -- Fiction; Secrets -- Fiction; Sailing -- Fiction; Deception -- Fiction; Families -- Fiction; Mystery and detective stories; Preparatory schools -- Juvenile fiction; Secret societies -- Juvenile fiction; Social classes -- Juvenile fiction; Sailing -- Juvenile fiction; Fraud -- Juvenile fiction; Family -- Juvenile fiction; Boston (Mass.) -- Juvenile fiction; Massachusetts -- Juvenile fiction; Boston (Mass.) -- Fiction; Massachusetts -- Fiction; Boston (Mass.) -- Juvenile fiction; Massachusetts -- Juvenile fiction; Detective and mystery stories; JUVENILE FICTION / Mysteries & Detective Stories; Detective and mystery fiction; Novels; Romans